Prevalence and risk factors of ischaemic stroke in the young: a regional Australian perspective. Issue 6 (14th June 2020) - Siriratnam, Pakeeran; Godfrey, Amelia; O'Connor, Ellie; Pearce, Dora; Hu, Chih‐Chiang; Low, Ashlea; Hair, Casey; Oqueli, Ernesto; Sharma, Anand; Kraemer, Thomas; Sahathevan, Ramesh
Abstract: Background: There is no universally accepted age cut‐off for defining young strokes. Aims: We aimed to determine, based on the profile of young stroke patients in our regional centre, an appropriate age cut‐off for young strokes. Methods: A retrospective analysis of all ischaemic stroke patients admitted to our centre from 2015 to 2017. We identified 391 ischaemic stroke patients; 30 patients between the ages of ≤50, 40 between 51–60 inclusive and 321 ≥ 61 years of age. We collected data on demographic profiles, risk factors and stroke classification using the Trial of Org 10 172 in Acute Stroke Treatment criteria. Results: We found significant differences between the ≤50 and ≥61 age groups for most of the risk factors and similarities between the 51–60 inclusive and ≥ 61 age groups. At least one of the six risk factors assessed in the study was present in 86.7% of the youngest group, 97.5% of the intermediate age group and 97.2% in the oldest group. In terms of the mechanisms of stroke, the youngest and oldest age groups in our study differed in the prevalence of cryptogenic, cardioembolic and other causes of stroke. The middle and older age groups had similar mechanisms of stroke. Conclusions: The prevalence of vascular risk factors and mechanisms of stroke likewise differed significantly across age groups. This study suggests that 50 years is an appropriate age cut‐off for defining young strokes and reinforces the importance of primary prevention in all age groups.